Implementation of the Independent Learning Curriculum in Islamic Education Subject at SMK Penerbangan Bina Dhirgantara - Rosita, Anggun Kurnia; Muhammad Wildan Shohib (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to describe the implementation of the Independent Learning Curriculum and the supporting and inhibiting factors at SMK Penerbangan Bina Dhirgantara Surakarta. This research uses a descriptive qualitative method with a phenomenological approach. The data collection techniques are through interviews, observations, and document analysis. Data validity uses source and technique triangulation. Data analysis techniques involve data reduction, data presentation, and conclusion drawing. The research results on implementing the Merdeka Curriculum at SMK Penerbangan Bina Dhirgantara Surakarta have yet to be fully optimal; several aspects must be improved and corrected so that its implementation runs well and optimally. Supporting factors in implementing the Merdeka Curriculum are the increased creativity of educators and students in their learning enthusiasm and student activity in the learning process, as well as enhancing educators' potential in developing their self-capacity. However, obstacles are felt in implementing the Merdeka Curriculum in Islamic Religious Education, such as the difficulty in creating quality learning because some teachers still do not master technology and have not fully understood the Merdeka Curriculum.